Executive function in school-aged children with cerebral palsy: Relationship with speech and language. (July 2018) - Sakash, Ashley; Broman, Aimee Teo; Rathouz, Paul J.; Hustad, Katherine C.
Highlights: This study provides new information concerning the relationship between speech, language and EF in children with CP. Children with CP may be at risk for EF difficulties regardless of their speech or language abilities. It is critical that the susceptibility for EF deficits be recognized by interventionists working with children with CP. Abstract: Background and Aims: Although children with cerebral palsy (CP) are at an increased risk for developing speech, language, and executive function (EF) impairments, little is known regarding the relationship among these risk factors. The current study examined how different profiles of speech and language impairment might be associated with impairments in EF skills in school-aged children with CP. Methods and Procedures: Forty-seven school-aged children with CP were included. Each child contributed between one and four data points for a total of 87 data points. Children were classified into speech and language profile groups at each data point. EF skills were examined using the Behavior Rating Inventory of Executive Function questionnaire. Outcomes and Results. Compared to a mean of 50 from a normative population of children, mean scores on all measures of EF were significantly elevated for all groups (p<.05). The proportion of children with CP with elevated EF scores was significantly higher for all groups compared to the expected proportion in a normal population of children (p<.05). Conclusions and Implications: Children with CP who do not have impairments in speech or language may be at risk for EF difficulties which may negatively affect social communication, academic performance, and functional independence.